Cross border claims against third parties without a contract with the claimant and package travels; judgment of the CJEU, 26 march 2020, Libuše Králová vs. Primera Air Scandinavia A/S (C-215/18): please mind the gap between the passenger and the air company! - Ruiz Martín, Anna María (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
In the case analysed, the Judgement of the Court of Justice of the European Union (CJEU), –C-215/08–the CJEU highlights, once again, the scope of application and principles that rule the different fora established in the Brussels Regulation/Brussels I bis Regulation related to consumers protection and contractual obligations, when the claimant is a passenger of an operating airline. By means of these fora, passengers which have been affected for an infringment committed by the air company that is usually based on a different Member State, might bring cross border actions so as to seek for compensation; however, the seize of a proper forum in these cases, it will depend on the characterization of the claim. In this case, the passenger did not celebrate the contract with the air company, but with a Travel Agency located on her same Member State (Czech Republic). With regard to the features of this case, the ECJ has also to take into consideration the Directive 90/314/CEE, on Package travel and Regulation (EC) nº 261/2004, on compensation and assistance to passengers.
Keywords: matters relating to a contract; contract; cross-border claims; compensation; place of performance; consumers; air carriage; passengers; package travel; characterization; restrictive interpretation; locus standi (passive).